(untitled) (Nigerian Journal of Technology, 2017)
This study investigated the effect of integrating various models proposed to improve a simple gas turbine power plant. A computer program was developed in Matlab software was used to simulate the performance parameters. The energy and exergy analysis of the plant was carried out. The energy and exergy analysis result revealed that both energy and exergy efficiency of plant is low as a result three improvement options were considered. They include Model 1: reducing inlet air cooling (IAC) of the compressor by using the wasted energy in the natural gas pressure drop station. Model 2: recovering wasted energy in the exhaust through heat recovery steam generator (HRSG) and injecting steam into the combustion chamber and lastly Model 3: by combining the two methods. The result showed that among the three methods of improving the plant investigated Model 3 was found to boost power output of the plant from 28.3 MW to 78.4 MW while the thermal and exergetic efficiency improved by 25.5 and 23.6% respectively. Furthermore, from economic and environmental point of view, the lowest levelized cost of electricity as well as the specific emissions was observed in Model 3. Consequently, Model 3 is selected as the best option in improving the simple gas turbine. http://dx.doi.org/10.4314/njt.v36i3.27